PROSEDUR PERHITUNGAN, PEMUNGUTAN, PENCATATAN, PENYETORAN, DAN PELAPORAN PPH PASAL 22 ATAS PENJUALAN BAHAN BAKAR DI PT. ABC - INDRIANI LESTARI; HUMALA SETIA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study was to determine the process of calculating, collecting, recording, depositing, and reporting of Income Tax Article 22 on the sale of fuel at PT. ABC and PT. ABC Transit Terminal 1, for the period January to December 2015. The study was also to test the compliance of the taxpayer to demonstrate the certainty of tax laws in Indonesia. Data for this study consisted of data and analysis in order to provide a clear picture. This study used a descriptive analysis for research and factual data. The object of this research is PT. ABC and PT. ABC Transit Terminal 1 for the period January to December 2015. The author uses the technique of collecting primary and secondary data of the person responsible and notes. It can be concluded as follows. First, the collection and recording of Income Tax Article 22 is done automatically through the ERP system. Income Tax Article 22 from the sale of fuel to gas stations PT. ABC collected by multiplying the rate of 0.25% with prices before VAT, fuel sales to other than an agent / distributor PT. ABC collected by multiplying the rate of 0.3% with prices before VAT, sales of CNG to the agent / distributor PT. ABC collected by multiplying the rate of 0.3% with the price before VAT, as well as the deposit and reporting is done on the date on or before the maturity date. Second, the process of calculating, collecting, recording Income Tax Article 22 carried out by PT. ABC and reporting of Income Tax Article 22 carried out by PT. ABC Transit Terminal 1, for the period January to December 2015 in accordance with Article 22 of Income Tax regulations in Indonesia.